Acquired pial arteriovenous fistula secondary to cerebral cortical vein thrombosis: A case report and review of the literature. Issue 4 (August 2022) - Sammoud, Skander; Hammami, Nadia; Turki, Dhaker; Nabli, Fatma; Sassi, Samia Ben; Belal, Samir; Drissi, Cyrine; Hamouda, Mohamed Ben
Pial arteriovenous fistulas (AVFs) are rare neurovascular malformations. They differ from arteriovenous malformations (AVMs) in that they involve single or multiple feeding arteries, draining directly into a dilated cortical vein with no intervening nidus. Pial and dural AVFs differ in blood supply, as the first originate from pial or cortical arteries and the latter from outside the dural leaflets. Unlike dural AVFs, most of the pial AVFs are supratentorial. The vast majority are congenital, manifesting during infancy. Acquired pial AVFs are significantly rarer and occur after vasculopathy, head trauma, brain surgery, or cerebral vein thrombosis. We describe a unique case of an acquired pial AVF in a 50-year-old man secondary to a cortical vein thrombosis manifesting as a focal-onset seizure with secondary generalization. A cerebral digital subtraction angiography revealed a low-flow pial AVF fed by a postcentral branch of the left middle cerebral artery draining to the superior sagittal sinus via a cortical vein. It also showed a collateral venous circulation adjacent to the previously thrombosed left parietal vein. There was no evidence of an associated dural AVF or venous varix. Endovascular treatment was scheduled three months later, but the angiogram preceding the embolization showed spontaneous and complete closure of the malformation. To our knowledge, this is the first case illustrating acquired pure pial AVF unaccompanied by a dural component following cortical vein thrombosis, eventually resulting in an unprompted closure.